Finding common ground: co-producing national soil policy in Wales through academic and government collaboration - Sánchez-García, Carmen; Button, Erik S.; Wynne-Jones, Sophie; Porter, Helen; Rugg, Ian; Hannam, Jacqueline A. (Elsevier, 2023)
Several agricultural reforms are in progress in the UK following its withdrawal from the EU. This is an opportunity to formulate a Welsh Soils Policy Statement (SPS) that raises the status of soils and ensures that their protection and sustainable management are integrated into future policy. We share and reflect on our novel approach at co-producing a SPS for Wales involving academic researchers and policy teams and provide clear insights into soil policy development. Building consensus among the various government departments and agencies formed the basis of our approach. For pragmatic reasons, it was decided to focus on agricultural soils, which cover 85% of Wales. A rigorous evidence review and synthesis formed the foundation for the development of the SPS, which devises a vision, and primary and secondary objectives for Welsh agricultural soils. A first draft was conceived by the researchers, with further iterations developed between the researchers and the policy team. The researchers were embedded into the policy teams, and this proved to be an effective mechanism for evidence-based policy development that also enhances the science-policy relationship in the longer term. New structures and incentives that promote the engagement between researchers and policymakers should be developed to support environmental policymaking across the board.
Keywords: Evidence-based; Science-policy interface; Soil governance; Soil security